Diversity and conservation status of amphibians and reptiles in cities: a country- level approach using citizen science - Álvaro Luna; David León--Muez; Martiño Cabana; Emilio Rosillo Parra; Santiago Delgado; Mauricio Santa; José Luis Molina-Pardo; Julián Cendrero Ramos; Sergi García-Rodríguez; Guillem Pascual; Sergio Cortés Merino; Rafael Tamajón Gómez; et al. (European Journal of Wildlife Research, 2026)

Short-Duration High-Intensity Exercise Impacts Oxidant and Antioxidant Markers in Elite Military Pentathlon Athletes with Sex-Based Variations - Marcio Antonio de Barros Sena; Danielli Braga de Mello; Paula Fernandez Ferreira; Renan Muniz-Santos; Marcos de Sá Rego Fortes; Thiago Dias Sales; Daniel Parada Theodoro; L. C. Cameron; Marcos Dias Pereira (Journal of Science in Sport and Exercise, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Direct-Fed Microbials Positively Influence Intestine Histomorphometry, Liver Histopathology and Apoptosis Modulation in Weaned Piglets Fed with Naturally Contaminated Aflatoxin B1 Diet - AL Cristofolini; V. Poloni; M. Fiorimanti; A. Magnoli; J. Parada; K. Gómez; CG Barbeito; C. Merkis; L. Cavaglieri (Current Microbiology, 2026)

On the Relationship Between Atmospheric Events of the Von Kármán Streets in the Robinson Crusoe Island and South Pacific Climate Variability - C. Amaya‐Cárcamo; C. Parada; B. Dewitte; M. Jacques‐Coper; S. Cornejo‐Guzmán (International Journal of Climatology, 2025)
The Juan Fernández Archipelago (JFA), located approximately 700 km off the Chilean coast, is of great scientific importance for its unique ecosystem and numerous endemic species. Designated a World Biosphere Reserve by UNESCO in 1977, it comprises three islands: Alejandro Selkirk (AS), Robinson Crusoe (RC) and Santa Clara (SC). Using satellite images of clouds, we identified and examined Von Kármán atmospheric vortex streets (VKSs) forming dipolar structures near the islands, a phenomenon rarely studied due to observational limitations. Based on visual inspection of satellite imagery, an average of three atmospheric VKSs events are recorded per year in the RC‐SC region over the period 2000–2020. Our study aims to characterise VKSs events in RC island through satellite observations and atmospheric reanalysis, while assessing their potential impact on the surrounding ocean dynamics using sea surface temperature (SST) data. We find that low‐level wind patterns, particularly prevalent in spring and summer, play a crucial role in the formation of VKSs, along with wind speeds that do not exceed 15 m/s. These conditions can occur during specific phases of regionally significant climate modes, such as the Interdecadal Pacific Oscillation (IPO), El Niño‐Southern Oscillation (ENSO), and variability in the subtropical South Pacific anticyclone. The activity of these modes is quantified by indices such as the Pacific Interdecadal Oscillation Tripole Index (TPI), Southern Oscillation Index (SOI), and South Pacific Subtropical Anticyclone Index (iASPS), highlighting a connection between VKS occurrence and large‐scale climate variability. We also observed elevated SST in the leeward RC during spring VKS events, potentially independent of the island mass effect. Our findings provide insights into the atmospheric and oceanic interactions shaping this unique island ecosystem.

Sitting time and risk of cancer incidence and cancer mortality in postmenopausal women: the Women’s Health Accelerometry Collaboration - Eric T. Hyde; Kelly R. Evenson; Annie Green Howard; Humberto Parada,; Chongzhi Di; Michael J. LaMonte; John Bellettiere; Carmen C. Cuthbertson; I-Min Lee; Andrea Z. LaCroix (Cancer Causes & Control, 2025)
Purpose Few studies have explored whether accelerometer-measured sedentary behavior increases cancer risk. We examined the associations of accelerometer-measured daily sitting time and mean sitting bout duration classified by the Convolutional Neural Network Hip Accelerometer Posture (CHAP) machine-learned algorithm with incidence of any cancer, incidence of 13 physical activity-related cancers, and cancer mortality among postmenopausal women. Methods We used data from 22,097 women (mean age = 73.3 years, standard deviation [SD] = 6.7) in the Women’s Health Accelerometry Collaboration, a consortium of two US-based cohort studies of postmenopausal women: the Women’s Health Study and the Women’s Health Initiative Objective Physical Activity and Cardiovascular Health Study. Women who completed hip-worn triaxial accelerometry for ≥ 4 of 7 consecutive days were included. Associations between sedentary behaviors and physician-adjudicated invasive cancer incidence and mortality were tested using Cox regression. Results Women were followed on average 8.0 years to identify cancer cases ( n = 1,861) and deaths ( n = 601). Overall, mean sitting time was 567 (SD = 113) min/day and mean sitting bout duration was 12.8 (SD = 4) min/bout. In covariate-adjusted models, one-SD increment higher in sitting time was associated with a 6% increased risk of incident cancer (hazard ratio [HR] = 1.06, 95% CI: 1.01–1.11); associations were similar for bout duration (HR = 1.05, 95% CI: 1.00–1.10). Estimates were similar for the 13 physical activity-related cancers (sitting time: HR = 1.10, 95% CI: 1.04–1.17; bout duration: HR = 1.08, 95% CI: 1.02–1.14) and for cancer mortality (sitting time: 1.06, 95% CI: 0.98–1.16; bout duration: HR = 1.05, 95% CI: 0.97–1.13). Conclusion Among postmenopausal women, sedentary behavior was associated with increased cancer risk, particularly for physical activity-related cancers and cancer mortality.

Shifts in Phenology and Species Ranges Synergistically Alter the Timing and Species Composition of the Flowering Season - Tadeo H. Ramirez‐Parada; Isaac W. Park; Shijia Peng; Misako Nishino; John T. Kartesz; Sydne Record; Charles C. Davis; Susan J. Mazer (Global Change Biology, 2025)
Global change is altering the phenology and geographic ranges of flowering species, with potentially profound consequences for the timing and composition of floral resources and the seasonal structure of ecological communities. However, shifts in flowering phenology and species distributions have historically been studied in isolation due to disciplinary silos and limited data, leaving critical gaps in our understanding of their combined effects. To address this, we used millions of herbarium and occurrence records to model phenological and range shifts for 2837 plant species in the United States across historical, recent, and projected climate and land cover conditions, enabling us to scale responses from species to communities, and from local to continental geographies. Our analysis reveals that communities are shifting toward earlier, longer flowering seasons in most biomes, with co‐flowering species richness increasing at the edges of the season and declining at historical peaks—trends projected to intensify under ongoing environmental trends. Although range and phenology shifts operate concurrently, they predominantly affect different aspects of the flowering season: phenological changes primarily alter seasonality—its start, end, and duration—and co‐flowering diversity at the edges of the season, while range shifts more strongly influence co‐flowering species richness during historical seasonal peaks and the identity and degree of flowering synchrony among co‐occurring species pairs. Together, these results demonstrate that shifts in phenology and species ranges act synergistically to restructure the flowering seasons across the conterminous United States, revealing wide variation in the pace and direction of change among biomes.

Functionality of the MYB1 Transcription Factor in the Transactivation of Leucoanthocyanidin Reductase (LAR) Promoters of Fragaria × Ananassa and Fragaria Chiloensis - Claudia Gómez-Parada; Carlos R. Figueroa; Kui Lin-Wang; Alejandra Moya-León; Richard V. Espley; Andrew C. Allan; Raul Herrera (Journal of Plant Growth Regulation, 2025)

Thermal seawater desalination for irrigation purposes in a water-stressed region: Emerging value tensions in full-scale implementation - Gonzalo Gamboa; Patricia Palenzuela; Rodoula Ktori; Diego C. Alarcón-Padilla; Guillermo Zaragoza; Samar Fayad; Dimitros Xevgenos; Mar Palmeros Parada (Desalination, 2025)

Sediment recycling during the Holocene marine transgression in Ría de Vigo (NW Iberia): multiproxy evidence and environmental implications - C. Muñoz Sobrino; A. Castro-Parada; V. Cartelle; N. Martínez-Carreño; C. Delgado; N. Cazás; I. Lázaro; S. García-Gil (Quaternary Science Reviews, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Sorption Parameters of Carbendazim and Iprodione in the Presence of Copper Nanoparticles in Two Different Soils - G. R. Tortella; O. Rubilar; M. Cea; C. Rodríguez-Rodríguez; A. Seguel; J. Parada (Journal of Soil Science and Plant Nutrition, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Buccal micronucleus cytome assay of populations under chronic heavy metal and other metal exposure along the Santiago River, Mexico - B. C. Gómez-Meda; G. M. Zúñiga-González; L. V. Sánchez-Orozco; A. L. Zamora-Perez; J. P. Rojas-Ramírez; A. D. Rocha-Muñoz; A. A. Sobrevilla-Navarro; M. A. Arellano-Avelar; A. A. Guerrero-de León; J. S. Armendáriz-Borunda; M. G. Sánchez-Parada (Environmental Monitoring and Assessment, 2017)

A geochemical approach to distinguishing competing tectono-magmatic processes preserved in small eruptive centres - Lucy E. McGee; Raimundo Brahm; Michael C. Rowe; Heather K. Handley; Eduardo Morgado; Luis E. Lara; Michael B. Turner; Nicolas Vinet; Miguel-Ángel Parada; Pedro Valdivia (Contributions to Mineralogy and Petrology, 2017)

The long-term survival of Acinetobacter baumannii ATCC 19606T under nutrient-deprived conditions does not require the entry into the viable but non-culturable state - Z. Bravo; M. Orruño; C. Parada; V. R. Kaberdin; I. Barcina; I. Arana (Archives of Microbiology, 2016)

South Pacific Integrated Ecosystem Studies meeting: toward conservation and sustainable use of marine resources in the South Pacific - C. Parada; S. Frusher; R. H. Bustamante; E. Di Lorenzo; P. Bernal; M. Cryer; A. Dunn; R. Garreaud; M. Gutierrez; S. Jennings; A. Montecinos; S. Neira; et al. (Fisheries Oceanography, 2016)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Sinorhizobium fredii HH103 does not strictly require KPS and/or EPS to nodulate Glycyrrhiza uralensis, an indeterminate nodule-forming legume - Isabel Margaret-Oliver; Wang Lei; Maribel Parada; Miguel A. Rodríguez-Carvajal; Juan C. Crespo-Rivas; Ángeles Hidalgo; Antonio Gil-Serrano; Javier Moreno; Dulce N. Rodríguez-Navarro; Ana Buendía-Clavería; Javier Ollero; José E. Ruiz-Sainz; et al. (Archives of Microbiology, 2012)

Induction of halogenated vesicle transport in cells of the red seaweed Laurencia obtusa - Wladimir C. Paradas; Leonardo T. Salgado; Daniela B. Sudatti; Miriam A. Crapez; Mutue T. Fujii; Ricardo Coutinho; Renato C. Pereira; Gilberto M. Amado Filho (Biofouling, 2010)

Simulation of physically mediated variability in prey resources of a larval fish: a three‐dimensional NPZ model - S. HINCKLEY; J. M. NAPP; A. J. HERMANN; C. PARADA (Fisheries Oceanography, 2009)
A three‐dimensional biophysical nutrient–phytoplankton–zooplankton model was used to investigate the spatial and temporal dynamics of food resources for young walleye pollock in the western Gulf of Alaska, to further understanding of recruitment processes for pollock. We modeled nitrogen, phytoplankton, a large herbivorous grazer parameterized as Neocalanus spp. (the biomass dominant copepod in the Gulf), and the 13 stages (egg, naupliar and copepodite) of Pseudocalanus spp. (a major constituent of the diet of pollock) so that the appropriate size class of food for each size of larval pollock was represented. Model results identified an area between the Semidi and Shumagin Islands that may not be suitable as a nursery area early in the year due to low prey abundance. Modeled mesoscale eddies, previously hypothesized to be important for larval pollock retention in Shelikof Strait, contained higher prey concentrations than the surrounding waters when they were cyclonic. This work also help to understand the consistency of pollock spawning in time and space in Shelikof Strait, by examining the timing and location of prey availability which, along with transport, narrows the window for optimal spawning.

The Mantos Blancos copper deposit: an upper Jurassic breccia-style hydrothermal system in the Coastal Range of Northern Chile - L. E. Ramírez; C. Palacios; B. Townley; M. A. Parada; A. N. Sial; J. L. Fernandez-Turiel; D. Gimeno; M. Garcia-Valles; B. Lehmann (Mineralium Deposita, 2006)

From particles to individuals: modelling the early stages of anchovy ( Engraulis capensis/encrasicolus ) in the southern Benguela - C. Mullon; P. Fréon; C. Parada; C. Van Der Lingen; J. Huggett (Fisheries Oceanography, 2003)
Several individual‐based models (IBMs) have recently been developed to improve understanding of factors impacting on recruitment variability of anchovy ( Engraulis capensis/encrasicolus ) in the southern Benguela. These IBMs have focused on early life history stages (eggs through to post‐larvae) as it is thought that variations in anchovy recruitment strength are primarily driven by biological and/or physical factors impacting on these stages. The pelagic zone of the Benguela system constitutes an ideal system for studying the coupling between biological and physical processes; in the IBMs this coupling is obtained by releasing particles endowed with biological properties in the virtual currents resulting from the output of a hydrodynamic model of the southwestern coast of South Africa. The particles are tracked through virtual time and space and their final locations are assessed in terms of previously defined criteria deemed to promote successful recruitment. The aim of this paper is to provide a synthesis of the results of IBMs of the early stages of anchovy in the southern Benguela constructed to date. Emphasis is placed on the methodological aspects of these studies and on the sequential link of several simulation experiments of increasing complexity. In addition to improving understanding, such an approach allows for effective interplay between modelling experiments and surveys or laboratory experiments. Details of individual IBM experiments and their results have been published elsewhere.

Modelling the effect of buoyancy on the transport of anchovy (Engraulis capensis ) eggs from spawning to nursery grounds in the southern Benguela: an IBM approach - C. Parada; C.D. Van Der Lingen; C. Mullon; P. Penven (Fisheries Oceanography, 2003)
An individual‐based model (IBM) was used to investigate the effects of physical and biological variables on the transport via a jet current of anchovy ( Engraulis capensis ) eggs from spawning to the nursery grounds in the southern Benguela ecosystem. As transport of eggs and early larvae is considered to be one of the major factors impacting on anchovy recruitment success, this approach may be useful to understand further the recruitment variability in this economically and ecologically important species. By coupling the IBM to a 3D hydrodynamic model of the region called Plume, and by varying parameters such as the spatial and temporal location of spawning, particle buoyancy, and the depth range over which particles were released, we could assess the influences of these parameters on transport success. A sensitivity analysis using a General Linear Model identified the primary determinants of transport success in the various experimental simulations, and model outputs were examined and compared with patterns observed in field studies. Model outputs compared well with observed patterns of vertical and horizontal egg distribution. Particle buoyancy and area of particle release were the major single determinants of transport success, with an egg density of 1.025 g cm −3 maximizing average particle transport success and the western Agulhas Bank being the most successful spawning area. This IBM may be useful as a generic prototype for other upwelling ecosystems.

Jurassic extensional tectono-magmatism and associated mineralization of the El Faldeo polymetallic district, Chilean Patagonia: geochemical and isotopic evidence of crustal contribution - M. A. Parada; C. Palacios; A. Lahsen (Mineralium Deposita, 1997)